LINGUISTIC ANALYSIS OF PSEUDONYMS OF UZBEK WOMEN IN THE FIELD OF CREATIVTY AND ART - Nizomova Shakhnoza; Odilova Sevara (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article examines the lexical-semantic, nominative-motivational, and structural characteristics of pseudonyms used by Uzbek women in the creative and artistic fields, such as poets, journalists, scientists, singers, and dancers